Identification of best uses of private freight data to support planning needs in public road sector: udvidet resumé - M. Illemann, Thorbjørn; Karam, Ahmed; Hegner Reinau, Kristian; Vuk, Goran; H. Overgaard, Christian (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
As congestion on Danish roads is increasing, it is imperative that solutions be suggested for the issues caused by this, e.g. prolonged travel time, bottlenecks, etc. A first step towards reducing congestion is to provide public policy makers in road sectors with valuable knowledge on how the roads are being used by freight transport. This can be achieved through collecting freight data from private freight transport companies and analysing the collected data to derive analytics that can inform planning decisions on the road infrastructure. Because there exist many data analytics that can be derived from shared freight data, it is essential to identify which data analytics can efficiently support the decision-making processes. This study presents a proposed framework that can be used to help identify the best uses of shared freight data, which best fit the needs of their public sectors/organizations.